Cryomacroscopy of vitrification, Part II: Experimental observations and analysis of fracture formation in vitrified VS55 and DP6 - Steif, Paul S. (2005)
A new imaging device, termed a “cryomacroscope”, was used to observe macrofractures in the cryoprotectant cocktails DP6 and VS55. Details of the design and construction of the cryomacroscope were presented in Part I of this report, which focused on describing the apparatus and observations of crystallization. Part I and the current paper (Part II) describe events that occur as 1 mℓ of cryoprotectant contained in a glass vial is cooled from room temperature down to cryogenic temperatures (∼ −135°C). The presence of cracking, as well as patterns in their position and orientation, are found to be dependent on the cooling rate and on the specific cryoprotectant cocktail. Cracks, if present, disappear upon rewarming, although they appear to be sites for later preferential crystallization. Computations which predict temperatures and mechanical stresses are used to explain observations of cracking. In conjunction with these reports, additional photos of cryomacroscopy of vitrification, crystallization, and fracture formation are available at http://www.me.cmu.edu/faculty1/rabin/CryomacroscopyImages01.htm.